MEDIASI NILAI PELANGGAN DAN EFISIENSI TRANSAKSI PADA PENGARUH DIGITAL MARKETING TERHADAP KEPUASAN PELANGGAN - Dody Sakti Wijaya; Fitri Lukiastuti; Rieke Retnosary (Strategic: Journal of Management Sciences, 2025)
This research aims to examine the influence of digital marketing, customer value and transaction efficiency on customer satisfaction, the influence of digital marketing on customer value and transaction efficiency. Testing the mediating role of customer value and transaction efficiency on the influence of digital marketing on customer satisfaction. The population in this study were all customers of PT. Uwinfly has as many internet users as the sample size is 100 respondents. Analysis uses partial least squares (PLS) with the smartPLS analysis tool. The results of this research, digital marketing, customer value and transaction efficiency have a significant positive effect on customer satisfaction, digital marketing has a significant positive effect on customer value and transaction efficiency. Customer value and transaction efficiency mediate the positive influence of digital marketing on customer satisfaction. The implications of this research contribute to the theory of co-creation of customer value and transaction efficiency and analyze the consequences of digital marketing on customer behavior from the perspective of customer satisfaction.